Body Composition and Nutrients Dietary Intake Changes during COVID-19 Lockdown in Spanish Healthy Postmenopausal Women - Cristina Acedo; Raul Roncero-Martín; Antonio Sánchez-Fernández; Cristina Mendoza-Holgado; María Pedrera-Canal; Fidel López-Espuela; Purificación Rey-Sánchez; Juan D. Pedrera-Zamorano; Luis M. Puerto-Parejo; Jose M. Moran; Jesús M. Lavado-García (MDPI AG, 2022)
(1) Background: During the COVID-19 lockdown, high rates of physical inactivity and dietary imbalances were reported in both adults and adolescents. Physical separation and isolation not only have a significant impact on the performance of physical activity but also affect people's lives, particularly their dietary habits. In the present study, we aimed to examine whether or not bioelectrical impedance-derived body composition parameters and dietary habits were affected during the pandemic-associated lockdown in postmenopausal Spanish women. (2) Methods: Sixty-six women participated in the study (58.7 ± 5.4 years) before (between July-October 2019) and after (August-October 2020) the lockdown, which occurred as a consequence of the COVID-19 pandemic in Spain. Body composition parameters were measured by bioelectrical impedance analysis while dietary intake of proteins, fat, carbohydrates, and energy was measured by a food frequency questionnaire. (3) Results Regarding body composition, no differences were observed in fat mass in % (mean increase 0.05 (2.74); p = 0.567), fat mass in kg (mean increase −0.07 (4.137); p = 0.356) or lean mass in kg (mean increase 0.20 (1.424); p = 0.636). Similarly, no statistically significant differences were observed between the two study periods for any of the nutrients studied, nor for energy intake (p > 0.05 in all cases). (4) Conclusions: After comprehensively assessing body composition and dietary intake of protein, fat, carbohydrates, and energy before and after COVID-19 lockdown in healthy adult women in Spain no changes in the parameters studied were observed during the period analyzed in the women examined.